2001
DOI: 10.1590/s0100-879x2001000200003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radioinduced damage and repair capacity in blood lymphocytes of breast cancer patients

Abstract: Genetic damage caused by ionizing radiation and repair capacity of blood lymphocytes from 3 breast cancer patients and 3 healthy donors were investigated using the comet assay. The comets were analyzed by two parameters: comet tail length and visual classification. Blood samples from the donors were irradiated in vitro with a 60 Co source at a dose rate of 0.722 Gy/min, with a dose range of 0.2 to 4.0 Gy and analyzed immediately after the procedure and 3 and 24 h later. The basal level of damage and the radioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…With respect to radiation, several studies have demonstrated higher initial and/or residual DNA damage and lower repair rate following irradiation of PBL in vitro as compared to controls (68,69,(74)(75)(76). Likewise, several studies have shown similar increases in DNA damage and decreases in repair efficiency in response to in vitro treatment with chemical mutagens such as doxorubicin (77), N-methyl N-nitro N-nitrosoguanidine (70), bleomycin (78,79) and benzo(a)pyrene diolepoxide (72).…”
Section: Measuring Dna Damage In Pbl Of Cancer Patientsmentioning
confidence: 99%
“…With respect to radiation, several studies have demonstrated higher initial and/or residual DNA damage and lower repair rate following irradiation of PBL in vitro as compared to controls (68,69,(74)(75)(76). Likewise, several studies have shown similar increases in DNA damage and decreases in repair efficiency in response to in vitro treatment with chemical mutagens such as doxorubicin (77), N-methyl N-nitro N-nitrosoguanidine (70), bleomycin (78,79) and benzo(a)pyrene diolepoxide (72).…”
Section: Measuring Dna Damage In Pbl Of Cancer Patientsmentioning
confidence: 99%
“…This technique is simple, rapid, relatively inexpensive, and capable of detecting the DNA damage produced by a variety of mutagens in both plant and animal tissues [Tice et al, 2000;Kim et al, 2002]. It has been used for studies in DNA repair [Kim et al, 2002], radiation biology [Nascimento et al, 2001], apoptosis [Singh, 2000], human biomonitoring [Kassie et al, 2000;Dhawan et al, 2001;Faust et al, 2004;Bajpayee et al, 2005, and genetic toxicology [Dhawan et al, 2002;Siddique et al, 2005;Undeger and Basaran, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The assay is increasingly used in biomonitoring and epidemiological studies [Betti et al, 1994[Betti et al, , 1995Collins et al, 1997;Kassie et al, 2000;Dhawan et al, 2001;Bajpayee et al, 2002;Faust et al, 2004], where it is most often used to detect DNA damage in peripheral lymphocytes. Using the Comet assay, higher levels of DNA damage have been reported among persons exposed to a variety of chemicals [Hartmann et al, 1995;Yuspa and Shields, 1997;Awara et al, 1998;Andreoli et al, 1999;Lei et al, 2004] and ionizing radiation [Singh et al, 1995;Nascimento et al, 2001]. The DNA damage detected by the Comet assay also has been reported to vary with gender [Bajpayee et al, 2002], age [Singh et al, 1990[Singh et al, , 1991, habits, and lifestyle [Betti et al, 1994[Betti et al, , 1995Piperakis et al, 1998;Dhawan et al, 2001;Park et al, 2003;Hininger et al, 2004].…”
Section: Introductionmentioning
confidence: 99%